The Impact of Boycott Calls on West Java Muslim Investors' Intentions to Invest in Unilever Stock - Rosida, Rida; Utami, Suci Aprilliani (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study aims to examine the impact of boycott calls on Muslim investors' intentions to invest in Unilever stock, by analyzing how attitudes, subjective norms, perceived behavioral control, and expected return influence investment intentions. The study also investigates whether Islamic religiosity moderates these relationships. The boycott calls refer to public campaigns urging Muslims to avoid investing in or purchasing products from companies affiliated with Israel, such as Unilever. A total of 215 Muslim investors in West Java participated in this quantitative study using a causal descriptive research design. Data were analyzed using SEM-PLS through the SmartPLS 4 application. The findings indicate that attitudes, perceived behavioral control, and expected return have a positive and significant effect on investment intentions, while subjective norms do not. Islamic religiosity was found to moderate only the relationship between perceived behavioral control and investment intention, weakening its influence. The boycott context acts as an underlying factor that shapes investors' perceptions, especially regarding moral and religious concerns. The results offer practical implications for institutions such as the Indonesian Ulema Council (MUI) to provide accurate guidance to Muslim investors regarding companies associated with geopolitical or religious controversies.